WeGA-WebApp release 4.9.0 - Stadler, Peter; Schmidt, Jakob; Zheng, Xianghua; Ried, Dennis; Richts, Kristina; Schreiter, Solveig; Jakob, Charlene
WeGA-WebApp release 4.9.0 Main features replace external Beacon service #451 update csLink to version v2 #450 Changelog A detailed changelog can be found at https://github.com/Edirom/WeGA-WebApp/wiki/Changelog Full Changelog: v4.8.1...v4.9.0 License This work is available under dual license: BSD 2-Clause and Creative Commons Attribution 4.0 International License (CC BY 4.0)

Edirom/WeGA-ODD: v4.9.0 - Stadler, Peter; Neubert, Anna Maria; Schreiter, Soveig; Obert, Salome; Ried, Dennis

WeGA data package v4.9.0 - Stadler, Peter

Edirom/WeGA-ODD: WeGA ODD files release 4.7.0 - Stadler, Peter; Anna Maria, Neubert; Schreiter, Solveig; Obert, Salome; Ried, Dennis

Nachhaltige Softwareentwicklung - Von der Inhouse-Lösung zur Open Source-Community am Beispiel von MerMEId - Henny-Krahmer, Ulrike; Stadler, Peter

Musikwissenschaft und Digital Humanities - Stadler, Peter (Historische Musikwissenschaft. Gegenstand – Geschichte – Methodik)

Towards a Model for Encoding Correspondence in the TEI: Developing and Implementing <correspDesc> - Stadler, Peter; Illetschko, Marcel; Seifert, Sabine (Journal of the Text Encoding Initiative)
Keywords: Briefe; TEI

Digitale Edition zwischen Experiment und Standardisierung